2004
DOI: 10.1080/09540120412331292405
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Internet by gay and bisexual male escorts: sex workers as sex educators

Abstract: While prior studies have targeted street-based male sex workers as potential vectors of disease transmission, the number of men who work independently through Internet chat-rooms and other online endeavors has steadily increased. It is likely that these men differ substantially from their street-based counterparts in terms of sexual risk behaviors with their clients. The purpose of this study was to explore the ways in which the Internet has impacted the work of male escorts and their sexual practices with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 33 publications
1
60
0
4
Order By: Relevance
“…Nevertheless, after analyzing multiple variables associated with men engaged in sex work, different authors have concluded that the group of MSWs is very heterogeneous. As a consequence, generalizing results is difficult (West & de Villiers, 1993;; Parsons et al, 2004) and our knowledge of sexual behaviors or HIV transmission among MSWs is still insufficient (De Cai et al, 2009). In fact, considering the relevance of some social-cognitive theoretical models, more information about the personal and professional ofile is needed to explore their sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, after analyzing multiple variables associated with men engaged in sex work, different authors have concluded that the group of MSWs is very heterogeneous. As a consequence, generalizing results is difficult (West & de Villiers, 1993;; Parsons et al, 2004) and our knowledge of sexual behaviors or HIV transmission among MSWs is still insufficient (De Cai et al, 2009). In fact, considering the relevance of some social-cognitive theoretical models, more information about the personal and professional ofile is needed to explore their sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this narrow research focus, such studies have documented substantial differences between heterosexual female and gay online escorts' marketing patterns. Parsons et al (2004) noted within their study, that gay male escorts were more likely than female escorts to include their preferred sexual activities and physical assets in their biographical profiles. Agresti (2009) also noted that male to male advertisements focused, at times, explicitly on the specifics of the size, shape and description of the escort's genitals, as well as on how male escorts frequently make reference to their role in intercourse within their biographical sketches (i.e.…”
Section: Review Of the Literature Escort Services And The Internetmentioning
confidence: 99%
“…As others have documented, the appeal of the Internet is seemingly obvious for sex workers; providing them with the anonymity, convenience, and discretion to target and advertise to a particular type of clientele (Milrod and Martin 2012;Parsons et al 2004;Sanders 2005;Walby 2012). Online escort advertisement websites have allowed escorts the opportunity to attract and match with clients who otherwise would not have patronised sex workers on the street (Cunningham and Kendall 2009;Ashford 2009), particularly female clients seeking either male or female sex workers (Burghart 2015).…”
Section: Review Of the Literature Escort Services And The Internetmentioning
confidence: 99%
See 1 more Smart Citation
“…clients and masculine escorts (Parsons et al, 2004); to analyze the contents of sex sales on the Internet (Lee and Castle,2006;Veena, 2007;Castle & Lee, 2008;Pruitt & Krul, 2011;Blackwell & Dziegielewski, 2013); the discussion between clients about feminine prostitutes about health and sexual unprotection (Langanke & Ross, 2009); information masculine escorts provide to their clients (Lee-Gonyea, 2009); language used on the Internet by prostitution clients ( Blevins, & Holt, 2009); about services offered and the health status in brothels (Chin et al 2009); sexual preferences of clients paying sexual services (Milrod & Monto, 2012); unprotection of sexual practices requested by clients (Adriaenssens & Jef Hendrickx, 2012); characteristics of communication in the contact between sellers and purchasers of sex (Jonsson et al 2014); the new risks of contact between purchasers and sellers of sex on the Internet (Jones 2015); normalization of masculine prostitution thanks to Internet (MacPhail et al, 2015); analysis of commercialization of sex on the web of three European cities (Pajnik et al, 2016). But all these studies refer to advertisements on websites, to the chat between clients and masculine/feminine prostiutes, and in very few cases to advertisements in newspapers and magazines (Chivers & Blanchard, 1996), and none of them to advertisements of flyers (Rúa et al, 2016), because perhaps their distribution is not allowed in many countries (France and Portugal, frontier countries forbid it).…”
Section: Introduction and State Of The Art Reviewmentioning
confidence: 99%